2018
DOI: 10.1002/ejp.1226
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarization‐activated channels shape temporal patterns of ectopic spontaneous discharge in C‐nociceptors after peripheral nerve injury

Abstract: We show an involvement of HCN channels in the modulation of ectopic spontaneous discharges from C-nociceptors. This finding exposes a mechanism of nociceptive transmission enhancement and highlights the clinical relevance of peripheral HCN blockade for spontaneous pain relief during neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…In mouse nociceptors, block of both EPAC isoforms is necessary to block the hyperactivity, either by combining two EPAC inhibitors or an inhibitor for one isoform with genetic deletion of the second isoform (red x). The necessity of PKA in rat nociceptors for hyperactivity after SCI was reported previously (Bavencoffe et al, 2016), while the necessity of HCN channels for similar hyperexcitability has been reported in other injury models (Bernal and Roza, 2018, Djouhri et al, 2015, Djouhri et al, 2018, Emery et al, 2011, Young et al, 2014) and observed after SCI (A.G. Bavencoffe, C.W. Dessauer and E.T.…”
Section: Discussionsupporting
confidence: 73%
“…In mouse nociceptors, block of both EPAC isoforms is necessary to block the hyperactivity, either by combining two EPAC inhibitors or an inhibitor for one isoform with genetic deletion of the second isoform (red x). The necessity of PKA in rat nociceptors for hyperactivity after SCI was reported previously (Bavencoffe et al, 2016), while the necessity of HCN channels for similar hyperexcitability has been reported in other injury models (Bernal and Roza, 2018, Djouhri et al, 2015, Djouhri et al, 2018, Emery et al, 2011, Young et al, 2014) and observed after SCI (A.G. Bavencoffe, C.W. Dessauer and E.T.…”
Section: Discussionsupporting
confidence: 73%
“…Demyelination allows for ectopic relocation of Na v and K v channels along the exposed patches of axonal membrane, altering the normal excitability and prompting abnormal spontaneous firing of action potentials (Roza et al, 2003; Campbell and Meyer, 2006; Bernal et al, 2016; Bernal and Roza, 2018; Roza and Lopez-Garcia, 2008). In addition, loss of myelin could favor electrical coupling between fibers (Meyer et al, 1985; Bernal et al, 2016) and promote aberrant sprouting from demyelinated nodes (Griffin et al, 2010).…”
Section: Lpa and Neuropathic Painmentioning
confidence: 99%
“…For electrophysiological recordings, saphenous spared nerve injury was performed (SSNI) as it allows the simultaneous study of axotomized and non‐axotomized fibres with intact receptive fields (RFs) within the same ex vivo preparation and that produces a large number of fibres with ectopic spontaneous and evoked discharges as previously described (Bernal et al., 2016; Bernal & Roza, 2018). Briefly, nerve‐end neuromas were produced by a total section of one of the peripheral branches of the saphenous nerve.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have pointed out that the expression of regeneration associated genes might not be restricted to axotomized neurons, as shown for the increased expression of activating transcription factor 3 (ATF) in non‐injured neurons after spared nerve injury (SNI) in rats (Berta et al., 2017). Moreover, electrophysiological and behavioural studies in models of incomplete nerve injury have revealed abnormal functional properties in intact fibres as well as the development of hyperalgesia independent of injured fibres (Ali et al., 1999; Bernal et al., 2016; Bernal & Roza, 2018; Li et al., 2000; Michaelis et al., 2000; Wu et al., 2001).…”
Section: Introductionmentioning
confidence: 99%